Vascular smooth muscle BK channels limit ouabain-induced vasocontraction: dual role of the Na/K-ATPase as a hub for Src-kinase and the Na/Ca-exchanger - Orth, Tobias; Pyanova, Anastasia; Lux, Simon; Kaiser, Peter; Reinheimer, Isabel; Nielsen, Daniel Løgstrup; Khalid, Josef Ali; Rognant, Salomé; Jepps, Thomas A.; Matchkov, Vladimir V.; Schubert, Rudolf (The FASEB journal, 2024)
Large-conductance, calcium-activated potassium channels (BK channels) and the Na/K-ATPase are expressed universally in vascular smooth muscle. The Na/K-ATPase may act via changes in the intracellular Ca2+ concentration mediated by the Na/Ca exchanger (NCX) and via Src kinase. Both pathways are known to regulate BK channels. Whether BK channels functionally interact in vascular smooth muscle cells with the Na/K-ATPase remains to be elucidated. Thus, this study addressed the hypothesis that BK channels limit ouabain-induced vasocontraction. Rat mesenteric arteries were studied using isometric myography, FURA-2 fluorimetry and proximity ligation assay. The BK channel blocker iberiotoxin potentiated methoxamine-induced contractions. The cardiotonic steroid, ouabain (10−5 M), induced a contractile effect of IBTX at basal tension prior to methoxamine administration and enhanced the pro-contractile effect of IBTX on methoxamine-induced contractions. These facilitating effects of ouabain were prevented by the inhibition of either NCX or Src kinase. Furthermore, inhibition of NCX or Src kinase reduced the BK channel-mediated negative feedback regulation of arterial contraction. The effects of NCX and Src kinase inhibition were independent of each other. Co-localization of the Na/K-ATPase and the BK channel was evident. Our data suggest that BK channels limit ouabain-induced vasocontraction by a dual mechanism involving the NCX and Src kinase signaling. The data propose that the NCX and the Src kinase pathways, mediating the ouabain-induced activation of the BK channel, act in an independent manner.